Assessment of Helicobacter pylori eradication rate of triple combination therapy containing levofloxacin - Gülseren Seven,; Kubilay Çınar,; Mustafa YAKUT,; Ramazan İdilman,; Ali ÖZDEN, (Turkish Journal of Gastroenterology, 2019)
-